PERKEMBANGAN DESA BERDASARKAN INDEKS DESA MEMBANGUN DI KABUPATEN MEMPAWAH - Moan Bura, Franciscus Xaverius (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2021)
ABSTRACT The Village Progress and Independence Status status is a measure of village classification to determine interventions, both budgets and village development policies. This study described the status of Village Progress and Independence based on the Village Developing Index (VDI) in Mempawah Regency from 2018 to 2020, namely to describe the condition of Village Status and Village Independence and identify the causes of the changes. The data were collected from the official documents and the interviews with relevant informant. The data were analyzed deductively. Referring to the Village Developing Index in Mempawah Regency, the status of Village Progress and Independence has improved in Social, Economic, and Ecological aspects/environmental resilience. This increase was mainly marked by the emergence of several villages with Advanced and Independent IDM Status.